Design, Identification, and Evolution of a Surface Ruthenium(II/III) Single Site for CO Activation. (13th November 2020) - Kang, Liqun; Wang, Bolun; Thetford, Adam; Wu, Ke; Danaie, Mohsen; He, Qian; Gibson, Emma K.; Sun, Ling‐Dong; Asakura, Hiroyuki; Catlow, C. Richard A.; Wang, Feng Ryan
Abstract: Ru II compounds are widely used in catalysis, photocatalysis, and medical applications. They are usually obtained in a reductive environment as molecular O2 can oxidize Ru II to Ru III and Ru IV . Here we report the design, identification and evolution of an air‐stable surface [bipy‐Ru II (CO)2 Cl2 ] site that is covalently mounted onto a polyphenylene framework. Such a Ru II site was obtained by reduction of [bipy‐Ru III Cl4 ] − with simultaneous ligand exchange from Cl − to CO. This structural evolution was witnessed by a combination of in situ X‐ray and infrared spectroscopy studies. The [bipy‐Ru II (CO)2 Cl2 ] site enables oxidation of CO with a turnover frequency of 0.73×10 −2 s −1 at 462 K, while the Ru III site is completely inert. This work contributes to the study of structure–activity relationship by demonstrating a practical control over both geometric and electronic structures of single‐site catalysts at molecular level. Abstract : An air‐stable surface [bipy‐Ru II (CO)2 Cl2 ] single site is designed towards CO oxidation, while all other Ru III single sites are not active. The methodology is further extended to nine transition‐metal single‐site systems, enabling the use of surface coordination chemistry in heterogeneous catalysis.